FORMULASI DAN PERBANDINGAN UJI STABILITAS FISIK SEDIAAN GEL EKSTRAK DAUN KACAPIRING (GARDENIA JASMINOIDES ELLIS) DAN ACNES SPOT GEL DIPASARAN - Sofia Eliasari (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2021)
Background: The gardenia jasminoides ellis contain flavonoids which have antioxidant and the antibacterial effects. Traditional use requires a long preparation, so it is necessary to formulate preparations that are more practical and durable in storage. The gel preparation was chosen in the formulation because it dries easily, forms a film that is easy to wash off and provides a cooling feeling on the skin. The gel component affects of the stability of the gel. The stability tests need to be carried out to ensure the quality, safety and efficacy of the gel meets the expected specifications and is stable during storage. The aims of the study to determine the difference in of the physical stability of the gel preparation of Gardenia jaminoides ellis and acnes spot gel on the market and determine the concentration of gardenia jasminoides ellis extract which has the best physical stability. Methods: The research of the method is experimental laboratory. Simplicia was extracted using 96% ethanol as solvent. The extract was formulated in gel dosage form with a concentration of 0.5% (FI), 1% (FII) and 1.5% (FIII). The results of study: The physical stability of the preparation tested by organoleptic, homogeneity, pH test, adhesion test, viscosity test, hedonic test and gel stability test which were compared with gels on the market. The results of the physical stability of the preparation observed at room temperature, the pH of the market gel was more acidic than the gardenia jasminoides ellis extract. The viscosity of formula 3 is higher in viscosity. In the stability test, it was seen that from the three formulas and gels on the market there was no change in shape, color and odor.